Does tattoo exposure increase the risk of skin cancer? A population-based case-control study - Rietz Liljedahl, Emelie ; 0000-0001-8742-5383; Nielsen, Kari ; 0000-0002-7363-0455; Engfeldt, Malin; Saxne Jöud, Anna ; 0000-0001-7192-4911; Nielsen, Christel ; 0000-0003-3940-7847 (ISEE 2024: 36th Annual Conference of the International Society of Environmental Epidemiology, Chile, 2024-08-25, 2024)
BACKGROUND AND AIM[|]The incidence of skin cancer has risen sharply over the past 30 years - coinciding with the rapidly increasing tattoo trend. In Sweden, 20% of the population is tattooed. The link between tattoos and skin cancer needs to be investigated, due to the presence of carcinogenic chemicals in tattoo ink, and the lack of epidemiological studies of the association. We aimed to investigate the association between tattoo exposure, and cutaneous melanoma (CM) and cutaneous squamous cell carcinoma (cSCC).[¤]METHOD[|]CM in 2880 individuals, and cSCC in 2857 individuals, aged 20 to 60 years, and diagnosed 2014-2017 were identified in the Swedish National Cancer Register. Controls (3:1) were identified in the Swedish Total Population Register and frequency matched on sex and age. Participants answered a questionnaire for exposure assessment, including questions about lifestyle factors such as tattoos, and relevant confounders, such as sun exposure. Information on socioeconomic factors was retrieved from administrative population registers. The risk of CM and cSCC for tattooed individuals compared with non-tattooed was investigated using logistic regression rendering incidence rate ratios (IRR).[¤]RESULTS[|]The response rate was 59% among cases and 50% among controls. Of the participants, 22% (354/1598) of the CM cases and 15% (236/1364) of the cSCC cases had a tattoo before the index date, vs 20% (815/4097) of the CM controls and 18% (802/3749) of the cSCC controls. We found no increased risk of cutaneous squamous cell carcinoma (IRR, 0.86; 95% confidence interval [CI], 0.73–1.02), but an increased risk of overall melanoma (including melanocytic nevi with severe atypia) in tattooed individuals compared to non-tattooed (IRR, 1.23, 95% CI, 1.06-1.44). The results were mainly driven by superficial spreading melanoma (IRR, 1.37, 95% CI, 1.11-1.69).[¤]CONCLUSIONS[|]The results suggest that tattoos may be a new risk factor for cutaneous melanoma, but further studies are needed to establish causality.